Association Between Involvement in Basketball and Cognitive Functioning of Elite Male and Female Basketball Leagues Players in Nigeria - Aderonmu Kehinde ADEBAYO (Cluj University Press, 2024)
Sports are physical activity that consists of rules, competition, challenge, entertainment and uncertainties. Competitive sports could be seen as those sports governed by a set of rules or customs, which serve to ensure fair competition, and allow consistent adjudication of the winner. This study ascertained the association between level of involvement in basketball and cognitive functioning of elite male and female basketball premier league players in Nigeria. Descriptive survey research design was adopted for the study. The population comprised of male and female basketball players in Nigeria. A total of 240 (120 males from the Premier League and 120 females from the Zenith league) basketball players in Nigeria selected using simple random sampling technique. A self-constructed 15 item questionnaire titled Involvement in Competitive Sports and Cognitive Functioning (ICSCF) was used to elicit information on from the level of cognitive functioning of elite basketball players in Nigeria. The results showed that there are two groups of items. The first group is made of 15 items while the second group is made up of 15 items. The mean of first group was 3.1±1 while the mean of group two was 2.1±0.7. df =28 and P-value = -0.20. P < 0.05 this indicated that there was a significant association between the level of involvement of respondents in basketball and their level of cognitive functioning. The study concluded that coaches and trainers should combine both the practical and mental mode of trainings when preparing their athletes for competition for optimal performance outcomes. Article history: Received: 2024 April 15; Revised: 2024 May 28; Accepted: 2024 August 14; Available online: 2024 August 30; Available print: 2024 August 30